Aportes epistemológicos para o ensino religioso na escola: um estudo analítico-propositivo - Schock, Marlon Leandro (2012)
What is the proper object of Religious Education in school? This is the main question of this thesis, from which the following corollary problems derive: What is the comprehension and the theoretical-epistemological foundation of professors and researchers in the area concerning this object? What do the National Curriculum Guidelines for Religious Education (PCNER) state as regards this subject? What relevant approaches can be found in publications in this area s representative events? What can be found on this subject in the country s two most representative religious education online venues: the National Permanent Forum of Religious Education s (FONAPER) website and the Education and Religion Research Group s (GPER) website? In order to answer the main question of this research and offer epistemological input for Religious Education, the thesis is divided into two parts. In the first, an epistemological analysis of Religious Education is offered. It begins with exposure of the author s identity as a basis for reading and for the construction of the argument. The second chapter deals more specifically with the assessment of the current concept of what this object is. For this purpose, a field research analysis was carried out with professors and researchers in the area; analysis of the PCNER; of FONAPER s website guest book; of the topics of theses, dissertations and monographs posted on GPER s website; of the publications in events; and of the Pedagogical Book of Religious Education of the State of Paraná. The second part of the thesis, for the epistemological propositions, begins with the concept of religious phenomenon and the research of phenomenological approach; the second chapter seeks to offer subsidies for reflection as regards the sacred as numinous in Rudolf Otto and the Sacred of Attribution as a system of meanings. A reflection within the same perspective articulates the myth from the etymological, anthropological and literary rubric. In the last chapter, transcendence is dealt with in its ontological and cultural aspects, in its relation with the immanence, with the object of transcendence, with the means of transcendence, with education and, more specifically, with Paulo Freire s pedagogy.